2011
DOI: 10.1177/1753425911416022
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of 10-hydroxy-trans-2-decenoic acid on LPS-induced IL-6 production via reducing IκB-ζ expression

Abstract: The effect of 10-hydroxy-trans-2-decenoic acid (10H2DA), a major fatty acid component of royal jelly, was investigated on LPS-induced cytokine production in murine macrophage cell line, RAW264 cells. 10H2DA inhibited LPS-induced IL-6 production dose-dependently, but did not inhibit TNF-α production. 10H2DA inhibited LPS-induced NF-κB activation in a dose-dependent fashion. In addition, NF-κB activation induced by over-expression of either MyD88 or Toll/IL-1 receptor domain-containing adaptor inducing IFN-β (TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 30 publications
0
37
0
1
Order By: Relevance
“…A mechanism putatively linked to 10-HDA anti-inflammatory effect is the inhibition of LPS-induced NF-κB activation observed in the murine macrophage cell line RAW264 (Sugiyama et al, 2012). …”
Section: Royal Jellymentioning
confidence: 99%
“…A mechanism putatively linked to 10-HDA anti-inflammatory effect is the inhibition of LPS-induced NF-κB activation observed in the murine macrophage cell line RAW264 (Sugiyama et al, 2012). …”
Section: Royal Jellymentioning
confidence: 99%
“…As described in the introduction, the unusual free fatty acids of RJ have been shown to exhibit a variety of bioactivities such as antimicrobial, anti-inflammatory, immunomodulatory, and growth promoting activities [5][6][7][8][9][10][11]. However, no attention has been paid so far on the potential interactions of RJ fatty acids with free fatty acid receptors.…”
Section: Biological Significancementioning
confidence: 99%
“…Watanabe et al showed that the major specific hydroxy fatty acids (10-HDA and 10-hydroxydecanoic acid) of RJ activate transient receptor potential ankyrin 1 (TRPA1) receptor and such an activation induces thermogenesis and energy expenditure [6]. 10-HDA was found to inhibit LPS-induced IL-6 production and NF-κB activation in a dose-dependent manner [7], and to exert immunomodulatory effects on human monocyte-derived dendritic cells [8]. More recently, the in vitro anti-inflammatory effects of these RJ fatty acids as well as sebacic acid (decanedioic acid) was evaluated and compared in lipopolysaccharide-stimulated RAW264.7 macrophages [9], while the bactericide and anti-inflammatory activity of 10-HDA in human colon cancer cells was studied [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ω3-fatty acids, such as eicosapentaenoic acid and docosahexaenoic acid, are sources of resolvins, which exert potent anti-inflammatory and pro-resolving effects via inhibiting TLR signaling (1). Recently, we reported that 10-hydroxy-trans-2-decenoic acid (10H2DA), which is a principal lipid component of royal jelly, has inhibitory effects on lipopolysaccharide (LPS)-induced interleukin (IL)-6 and LPS-and interferon (IFN)-γ-induced nitric oxide (NO) production in murine macrophages (36,37,39). Royal jelly also contains 10-hydroxydecanoic acid (10HDA) at a high concentration (> 100 mM), which is almost same as that of 10H2DA.…”
mentioning
confidence: 99%